2021
DOI: 10.1111/tri.13863
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on the incidence of osteoporosis and fractures after liver transplant

Abstract: Following liver transplant (LT), osteoporosis is a severe complication that causes morbidity. However, the incidence and risk factors of osteoporosis and fractures have not been well described. Single-arm meta-analysis of studies reporting osteopenia, osteoporosis, and fractures post-LT was performed with meta-regression for study period. Dichotomous variables, continuous variables and time-to-event variables were pooled in odds ratio, weighted mean difference and hazard ratio, respectively. For risk factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 70 publications
0
4
0
1
Order By: Relevance
“…The reason for BMD reduction in the early posttransplant period may be due to the pre- and posttransplant changes in bone turnover state. A meta-analysis indicated that liver transplant recipients have a fivefold increased risk of both osteoporosis and fractures compared with non-LT recipients ( 37 ). The main risk factors for postliver transplant fractures include the presence of pretransplant fractures, decreased BMD, posttransplant glucocorticoid dose, and primary biliary cholangitis ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for BMD reduction in the early posttransplant period may be due to the pre- and posttransplant changes in bone turnover state. A meta-analysis indicated that liver transplant recipients have a fivefold increased risk of both osteoporosis and fractures compared with non-LT recipients ( 37 ). The main risk factors for postliver transplant fractures include the presence of pretransplant fractures, decreased BMD, posttransplant glucocorticoid dose, and primary biliary cholangitis ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…As individuals age, there is a progressive decrease in bone mineral density, primarily affecting trabecular bone due to its higher metabolic activity and turnover rate compared to cortical bone [96]. This age-related decline in BMD is influenced by factors such as hormonal changes, decreased physical activity, and impaired remodeling capacity due to decreased osteoblast-osteoclast function [97]. Therefore, one possibility of older individuals presenting for evaluation after trauma is unmasking previously subclinical osteoporosis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Even patients without a pretransplant history of osteoporosis face an elevated risk of posttransplant osteoporosis and fractures [12,13]. The incidence of fractures is four to five times higher compared to the general population [14,15] and can be attributed, in part, to the side effects of immunosuppressive agents such as glucocorticoids, cyclosporine A, and tacrolimus [16][17][18][19]. Particularly in individuals engaging in endurance sports, an imbalance between energy expenditure and caloric intake can lead to the relative energy deficiency in sport syndrome, further reducing bone mineral density and increasing the risk for stress fractures [20,21].…”
Section: Musculoskeletal Injuriesmentioning
confidence: 99%